A Parallel Pandemic: Increased Firearm Injuries at Five Northern California Trauma Centers During the COVID-19 Pandemic: An Interrupted Time-series Analysis. Issue 5 (14th May 2022) - Matthay, Zachary A.; Callcut, Rachael A.; Kwok, Amy M.; Aarabi, Shahram; Forrester, Joseph D.; Kornblith, Lucy Z.
Abstract : Objective: This study aimed to characterize changes in firearm injuries at 5 level 1 trauma centers in Northern California in the 12 months following the start of the COVID-19 pandemic compared with the preceding 4 years, accounting for regional variations and seasonal trends. Summary and Background Data: Increased firearm injuries have been reported during the early peaks of the COVID-19 pandemic despite shelter-in-place restrictions. However, these data are overwhelmingly from singlecenter studies, during the initial phase of the pandemic prior to lifting of shelter-in-place restrictions, or do not account for seasonal trends. Methods: An interrupted time-series analysis (ITSA) of all firearm injuries presenting to 5 adult level 1 trauma centers in Northern California was performed (January 2016to February 2021). ITSA modeled the association of the onset of the COVID-19 pandemic (March 2020) with monthly firearm injuries using the ordinary least-squares method, included month indicators to adjust for seasonality, and specified lags of up to 12 months to account for autocorrelation. Results: Prior to the start of COVID-19, firearm injuries averaged (±SD) of 86 (±16) and were decreasing by 0.5/month ( P < 0.01). The start of COVID- 19 (March 2020) was associated with an alarming increase of 39 firearm injuries/month ( P < 0.01) followed by an ongoing rise of 3.5/mo ( P < 0.01). This resulted in an average of 130 (±26) firearm injuries/month during the COVID-19 period and included 8 of the 10 highest monthly firearm injury rates in the past 5 years. Conclusions: These data highlight an alarming escalation in firearm injuries in the 12 months following the onset of the COVID-19 pandemic in Northern California. Additional studies and resources are needed to better understand and address this parallel public health crisis.